Audit Committee Characteristics, Profitability, and Audit Report Lag - Devi Novitasari Putri Wibowo; Rahmawati Rahmawati (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
Lag in the audit report is the delay in the completion of the independent auditor's report by the auditor who audits the client's financial statements. Financial statements need to be presented in a timely manner in order to be able to use them as a basis for decision making and to keep them current. This study examines the effect of the relationship between the characteristics of an audit committee and profitability on the delay of an audit report. The sample used is manufacturing companies listed on the Indonesian Stock Exchange in 2018-2020. Based on the purposive sampling criteria, hypotheses were tested on 302 companies using panel data regression analysis techniques. The results of the study indicate that there is a negative effect of audit committee gender and profitability on audit report lag.